Growth differentiation factor 10 induces angiogenesis to promote wound healing in rats with diabetic foot ulcers by activating TGF-β1/Smad3 signaling pathway - Zhao, Qingsong; Xu, Jinmei; Han, Xu; Zhang, Zheqi; Qu, Jiahui; Cheng, Zhifeng (Frontiers in Endocrinology, 2023)
Background: Diabetic foot ulcer (DFU) represents a highly-prevalent complication of diabetes mellitus (DM). Herein, the current study sought to identify the role of growth differentiation factor 10 (GDF-10) in wound healing in DFU via regulation of the transforming growth factor-beta 1 (TGF-β1)/Smad3 pathway. Methods: DM- and DFU-related microarray datasets GSE29221 and GSE134431 were firstly retrieved, and weighted gene co-expression network analysis (WGCNA) was carried out to construct a co-expression network affecting wound healing in DFU, followed by differential analysis. A protein-protein interaction (PPI) network of the DFU-related genes was subsequently constructed, and the core genes and signaling pathways in DFU were screened with the Gene Ontology and Kyoto Encyclopedia of Genes and Genomes functional analyses. A DFU rat model was constructed for mechanism verification of the effect of GDF-10 on wound healing in DFU. Results: WGCNA screened five co-expression modules, and the brown module was most closely-related to DM. Clustering analysis screened 4417 candidate genes, of which 175 differential genes were associated with wound healing, further involved in TGF-β1/Smad3 signaling pathway regulation of wound healing in DFU. The PPI network analysis predicted that GDF-10 might regulate the TGF-β1/Smad3 signaling pathway to participate in DFU development. Results of animal experimentation showed that the wound healing rates of NFU, DFU, DFU + GDF and GDF + SIS3 groups on the 22nd day were (87.66 ± 6.80)%, (56.31 ± 7.29)%, (71.64 ± 9.43)% and (55.09 ± 7.13)%, respectively. Besides, the expression of TGF-β1 in NFU, DFU, DFU + GDF and GDF + SIS3 groups was 0.988 ± 0.086, 0.297 ± 0.036, 0.447 ± 0.044, and 0.240 ± 0.050, respectively, and that of Smad3 was 1.009 ± 0.137, 0.145 ± 0.017, 0.368 ± 0.048, and 0.200 ± 0.028, respectively. Specifically, GDF-10 exerted a significant diminishing effect on fasting blood glucose level, and promoted wound healing in DFU rats, in addition to up-regulation of VEGF, FGF, Ang-1, TGF-β1, Smad3 and enhancement of IL-1b, IL-6, TNF-a and MMP-9, thereby promoting fibroblast proliferation, collagen deposition and angiogenesis. Conclusions: Our findings highlight that GDF-10 may promote angiogenesis by activating TGF-β1/Smad3 signaling, thereby promoting wound healing in DFU rats.